Local Government Finances The Link between Intergovernmental Transfers and Net Worth - de Mello, Luiz (OECD Economics Department Working Papers, 2007)
There is a large literature on how the sharing of revenue between different levels of government and the design of intergovernmental transfer schemes affect sub-national finances. Using a panel of OECD countries during 1980-2005, this paper tests for: i) the presence of a stable long-run statistical association between changes in transfer receipts and sub-national net worth and ii) the direction of causality between changes in transfer receipts and net worth. The main empirical findings are that, first, there is a stable long-term relationship between transfer receipts and local government net worth for the case of current, but not capital, transfers. An increase in intergovernmental transfer receipts is found to be associated with a modest reduction in the recipient jurisdiction's net worth over the long term, but a fall in net worth is associated with an almost one-to-one subsequent increase in transfer receipts. Second, the direction of causality is sensitive to the technique used to estimate the long-term parameters. One technique suggests that causality runs from transfers to net worth, which lends support to a large literature on the effect of cost-shifting on sub-national budget outcomes. But causality also appears to run from net worth to transfer receipts, suggesting that transfers may be used as a deficitfinancing tool